Upaya Peningkatan Hasil Belajar Siswa Kelas V Dengan Menerapkan Model Paired Story Telling - Sutarmi Sutarmi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to determine the increase in student learning outcomes in understanding light and its properties in the fifth grade science subject at SD Negeri 47 Lubuklinggau by using the paired story telling learning model. The method used in this research is the Classroom Action Research (CAR) method which begins with pre-action data and is carried out in two research cycles. The results showed that student learning outcomes in pre-cycle 9 students completed (33.33%) increased in cycle 1 to 18 students completed (66.67%) and in cycle 2 managed to increase to 24 students completed (88.89%). In conclusion, the Think Pair Share learning model can improve student learning outcomes on material about natural events. Keywords: Light, Paired Story Telling, PTK